Unpaid Care Work in the Republic of Belarus: Structure Analysis and Methods of Macroeconomic Assessment - Agabekova, N. V.; Korolenok, A. V. (Statistics of Ukraine, 2019)
Achieving gender equality is important for sustainable socio-economic development of the country. The significance of this problem is also reflected in the Sustainable Development Goals, namely, achieve gender equality (Goal 5). While the Republic of Belarus pays great attention to solving gender problems, inequality in the labor market is persisting. In particular, gender differences in the distribution of paid and care-related work still exist. Therefore, it is important to study and identify the differences in the time budget of employed men and women in the Republic of Belarus, with assessing the unpaid household services and their recording in national accounts. The article is devoted to the analysis of the time use structure in the Republic of Belarus, with determining the differences in the distribution of paid and unpaid work between men and women and assessing the housework that is “invisible” for a market economy. The study is based on the methodological approaches of the System of National Accounts and the updated international standards on labor statistics. Data from time-use surveys and sample household surveys on employment issues are used as the information base of our study. It is shown that the total daily working day of women lasts 68 minutes longer than the working day of men, which is explained by the fact that women spend twice longer time on housework than men. The unpaid work (services produced inside households) is valuated by the cost approach using the methods of full, specialized replacement and opportunity costs. The estimated scopes of the household work “invisible” for a market economy range from 12.6% to 20.5% of Gross Domestic Products in 2018. Future studies should focus on the assessment of the women’s contribution in the national economy, with inclusion of their housework and the household output for own final consumption in the traditional macroeconomic indicators.